2019
DOI: 10.1016/j.bpj.2019.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Modeling pH-Dependent NMR Chemical Shift Perturbations in Peptides

Abstract: Modeling the pH dependence of protein and peptide chemical shifts outside the range of physiological values (6.5-7) is key to understanding structure-function relationships of these systems. These capabilities are largely not available in current chemical shift prediction software. In this study, we utilize a combination of molecular dynamics and quantum mechanics to investigate the through-space and through-bond contributions of protonation-dependent chemical shift perturbations (CSPs) in model tripeptides. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…The upfield shifting is consistent with the findings from the molecular simulations of Artikis and Brooks 47 and the experiments of Platzer et al, 50 where they observed chemical shift perturbations of the δand εamino groups of lysine due to changes in the protonation state.…”
Section: Nmr Spectroscopysupporting
confidence: 90%
See 3 more Smart Citations
“…The upfield shifting is consistent with the findings from the molecular simulations of Artikis and Brooks 47 and the experiments of Platzer et al, 50 where they observed chemical shift perturbations of the δand εamino groups of lysine due to changes in the protonation state.…”
Section: Nmr Spectroscopysupporting
confidence: 90%
“…Changes in ionization cause alterations in the electronic environment around the atomic nuclei and result in different extents of shielding, causing chemical shifts to be perturbed from typical values. Chemical shift perturbations can occur through site‐specific changes in ionization or through electrostatic interactions that alter the electrostatic field around a nucleus 47–50 . 1D 1 H, 13 C‐{ 1 H} and 2D [ 1 H, 13 C] HSQC NMR spectroscopy data were used to identify the functional groups responsible for the specific NMR peaks observed and were tracked across the pH range of 2–12.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…via hydrogen bonds), which are not trivial to account for in DFT calculations. [15][16][17] Also vibrational contributions to the chemical shift are usually neglected.…”
Section: Introductionmentioning
confidence: 99%